2021
DOI: 10.3390/v13050812
|View full text |Cite
|
Sign up to set email alerts
|

Arsenicals, the Integrated Stress Response, and Epstein–Barr Virus Lytic Gene Expression

Abstract: Following our observation that clofoctol led to Epstein–Barr virus (EBV) lytic gene expression upon activation of the integrated stress response (ISR), we decided to investigate the impact of As2O3 on viral lytic gene expression. As2O3 has also been reported to activate the ISR pathway by its activation of the heme-regulated inhibitor (HRI). Our investigations show that As2O3 treatment leads to eIF2α phosphorylation, upregulation of ATF4 and TRB3 expression, and an increase of EBV Zta gene expression in lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…It has been shown that nel navir can decrease overall translation rates and facilitate transcriptional activity characteristic of the ISR [20]. We have also shown this recently with the antimicrobial drug, clofoctol and arsenic, in EBV positive cell lines [30,31]. This may be one of the mechanisms by which nel navir inhibits virus capsid maturation: by altering the expression of an essential structural protein.…”
Section: Kshv Virus Protein Expression In Nel Navir Treated Cellssupporting
confidence: 53%
See 1 more Smart Citation
“…It has been shown that nel navir can decrease overall translation rates and facilitate transcriptional activity characteristic of the ISR [20]. We have also shown this recently with the antimicrobial drug, clofoctol and arsenic, in EBV positive cell lines [30,31]. This may be one of the mechanisms by which nel navir inhibits virus capsid maturation: by altering the expression of an essential structural protein.…”
Section: Kshv Virus Protein Expression In Nel Navir Treated Cellssupporting
confidence: 53%
“…Three PCR Master Mixes were created to detect DNA sequences associated with the GAPDH, CHOP, and Trib3 genes. Each of the master mixes contained the Bio-Rad SsoFast EvaGreen supermix, RNase/DNase-free water, and forward and reverse primers [30,31] Immunoblots 5r219 cells (1 × 10 6 ) were harvested 72 h post-induction. Cell pellets were lysed in 2X Laemmli buffer and 10% of this sample was resolved using NuPAGE 4-12% Bis-Tris gels (Thermo Fisher) and transferred to nitrocellulose membranes using the iBlot2 system (Thermo Fisher), as described by Luitweiler et al [32].…”
Section: Rt Qpcrmentioning
confidence: 99%
“…Even at a low concentration, PM2.5 was significantly correlated with the incidence of SQC and AdC [202]. Importantly, arsenic trioxide (As2O3) is another environmental contaminant (present in water, air, and food) related to LC that can activate EBV lytic gene expression in epithelial cells [203]. However, As2O3 is also able to decrease cell proliferation, promote apoptosis, and exhibit anti-angiogenesis properties in the lungs, inhibiting tumor metastasis [204].…”
Section: Ebv Interactions With Other Environmental Contaminants In Lu...mentioning
confidence: 99%
“…Unlike As 2 O 3 , BTdCPU induced RNA expression of gp110 and gp350. Treatment with both drugs reversed this effect [ 166 ].…”
Section: Factors Involved In Ebv Reactivationmentioning
confidence: 99%